Rancang Bangun Pengenalan Sistem Informasi Sekolah Menengah Pertama (SMP) Bina Taruna Medan Berbasis Android Dengan Metode Rest API (Application Programming Interface) - Gedmi Sari Melati Rambe ,; Rita Novita Sari, (Student Scientific Creativity Journal, 2023)
Academic information systems are veritably important for schools, especially for academy and students. Still, the perpetration of the academy information system has not yet reached all educational institutions, for illustration at Bina Taruna Medan Middle School. Therefore, the author make an Android-based school information application, so students can view information about academy biographies, school facilities, school galleries, teacher names, subject schedules, and student grades through the application without having to go to academy. Therefore, in this study the authors used the Rest API (Application Programming Interface) method. The Rest API method is a software that allows developers to integrate and allow two different applications to connect to each other simultaneously. With the Android-based school application at Bina Taruna Medan Middle School, it is hoped that it will make it easier for students to get school information that is more accurate, effective and efficient, as well as make it easier for the school to collect information about student academic development. So from the results of black box testing, the results show that the system built can work well according to its function.